The Formation and Definition of the Concept of Home - Mirzaeva Nargizoy Sanjarovna (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
The article is devoted to the topic of world conceptualization, which is relevant for modern linguistics, as one of the most important cognitive procedures. The linguoculturological aspects of the formation and definition of the concept “home” are considered, that the specifics of its functioning in various fields are established.